Design of multiple collar stay antennas for wireless wearable compact devices. Issue 2 (1st October 2019) - Gautam, Baishali; Verma, Pooja; Singha, Anindita; Islam, Hashinur; Prakash, Om; Das, Saumya
Abstract: Design of wearable antennas for various uses demands satisfactory and reliable antenna performance for a long period time. Generally, microstrip patch antennas with textile material as a substrate are used for many wearable applications. But the characteristics of the textile materials like absorption of water, porousness of fabric material, thickness of fabric along with the movement of the human body leads to shifting of operating frequency, bandwidth, return loss, and the polarization of antenna. To resolve these issues, light weight, low profile, compact, rigid antennas have been developed in this research work. Collar stay of formal shirts has been considered to develop two conformal wearable microstrip antennas for ISM band and Wi‐Fi applications separately. The proposed conformal antennas yield a 10 dB impedance bandwidth of 30 and 76 MHz with center frequency 2.1 and 5.2 GHz, respectively. The maximum gain achieved with the proposed structures is 3.56 and 4.88 dBi for 2.1 and 5.2 GHz, respectively. Measurement of specific absorption rate (SAR) on an artificial human head model has also been conducted for 2.1 GHz antenna on software platform to justify the acceptance of proposed antenna for wearable applications. It is found that the electromagnetic energy absorbed by the head model is restricted to a maximum SAR value 0.127 and 0.066 W/kg over 1 and 10 g average tissue mass respectively at 2.1 GHz. The antenna radiation pattern under wearable condition has also been presented.